A Solution‐Processed Hole‐Transporting Layer Based on p‐Type CuCrO2 for Organic Photodetector and Image Sensor. Issue 20 (24th September 2021) - Li, Yi; Luo, Hongde; Mao, Longmei; Yu, Longxin; Li, Xifeng; Jin, Libo; Zhang, Jianhua
Abstract: In this study, p‐type delafossite CuCrO2 nanomaterials are synthesized via a one‐step hydrothermal reaction. An organic photodiode (OPD) with an inverted stack is fabricated by utilizing such CuCrO2 as the hole‐transporting layer. The single OPD device shows the dark current density of 6.48 × 10 −8 A cm −2, and an external quantum efficiency of 16.2% at a 525 nm illumination, and a −5 V bias. Its responsivity and detectivity are 68.5 mA W− 1 and 4.75 × 10 11 cm Hz 1/2 W −1, respectively. A large‐area, flat‐panel image sensor is also realized similarly by applying the materials and structure onto a thin‐film transistor backplane. The active area and pitch of flat‐panel sensor are 75.0 mm × 81.0 mm and 150 µm, respectively and its resolution is 510 × 470. The performance of the organic image sensor is evaluated. The results indicate the materials and device have potential applications for the flat‐panel detector. Abstract : An improved hydrothermal synthesis of delafossite metal oxides (CuCrO2 ) is proposed and found that isopropanol is suitable as a dispersant to prepare films on the active layer. Based on the cost‐effective and room‐temperature solution‐processed CuCrO2 hole‐transporting layer, a top‐illuminated organic photodetector and image sensor based on the vertical structure with a simple architecture and fabrication process exhibits a high‐resolution and a weak‐light imaging capability.